2008
DOI: 10.1074/jbc.m803742200
|View full text |Cite
|
Sign up to set email alerts
|

Elongin B/C Recruitment Regulates Substrate Binding by CIS

Abstract: SOCS proteins play a major role in the regulation of cytokine signaling. They are recruited to activated receptors and can suppress signaling by different mechanisms including targeting of the receptor complex for proteasomal degradation. The activity of SOCS proteins is regulated at different levels including transcriptional control and posttranslational modification. We describe here a novel regulatory mechanism for CIS, one of the members of this protein family. A CIS mutant deficient in recruitment of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…In mammals, SH2 domain is a target recognition motif commonly found in tyrosine kinases and involved in protein-protein interaction with phosphotyrosine residues (Machida & Mayer 2005 (Hilton 1999). Similar to SH2 domain, SOCS box also plays a role in SOCS inhibition of cytokine signaling as it can interact with elongin B/C, culin B, and Ring-box 2 to form a complex with E3 ubiquitin ligase activity (Yoshimura et al 2007) and trigger proteasomal degradation of JAK 2 by SOCS binding (Piessevaux et al 2008a). The presence of structural motifs in grass carp Socs1-3 and Cish for signal termination of JAK/STAT pathway raises the possibility that the type II SOCS in fish model may also participate in the down-regulation of cytokine signaling in a way similar to mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, SH2 domain is a target recognition motif commonly found in tyrosine kinases and involved in protein-protein interaction with phosphotyrosine residues (Machida & Mayer 2005 (Hilton 1999). Similar to SH2 domain, SOCS box also plays a role in SOCS inhibition of cytokine signaling as it can interact with elongin B/C, culin B, and Ring-box 2 to form a complex with E3 ubiquitin ligase activity (Yoshimura et al 2007) and trigger proteasomal degradation of JAK 2 by SOCS binding (Piessevaux et al 2008a). The presence of structural motifs in grass carp Socs1-3 and Cish for signal termination of JAK/STAT pathway raises the possibility that the type II SOCS in fish model may also participate in the down-regulation of cytokine signaling in a way similar to mammals.…”
Section: Discussionmentioning
confidence: 99%
“…A major function of this family is inhibition of cytokine receptor signaling (Piessevaux et al, 2008a, 2008b). Transcriptional activation of SOCS genes usually occurs by the same cytokine signaling pathways they inhibit (Matsumoto et al, 1997; Pezet et al, 1999; Tollet-Egnell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The SOCS box is involved in the formation of an E3 ubiquitin ligase complex with Elongin B/C, Cullin (CUL), and ring finger (RBX) proteins (Babon et al, 2008; Kamura et al, 1998, 2004; Piessevaux et al, 2008a, 2008b; Zhang et al, 1999). SOCS proteins function as part of the E3 ubiquitin ligase complex, increasing the degradation of a number of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed analysis using CIS mutants revealed that CIS binding to the LR and EpoR not only depends on its SH2 domain but also on its SOCS box, with a critical role for the CIS Tyr-253 and the Elongin B/C recruitment site. Much in contrast, the SOCS box of SOCS2 does not play a role in substrate binding [11,12].…”
Section: Lrmentioning
confidence: 99%